Musical Instrument Industry During the Paleolithic AgeA case study of the flute (the oldest human musical instrument) (Damascus University Journal of Historical Studies, 2023)
This research deals with the flute industry during the Paleolithic Age, and the study area is limited to the European continent only as a result of the absence of archaeological detectors related to the research in the rest of the world's other geographical areas. This research depends on its communication, which accommodates all the flutes discovered in the Paleolithic Age sites in an integrated single work, which is an urgent need to understand the early root of music in general, and the flute instrument in particular. The research follows the descriptive approach in an analytical manner and begins to describe the discoveries in each location separately in terms of dimensions, the number of holes and its positions, and the flute’s conditions of damage, its manufacture in addition to its date. Finally, it should be noted that the source of the basic information in this research is the study that addresses the discovered flutes in the European archaeological sites related to the Middle and Upper Paleolithic Age.
Keywords: Musical Instruments; The Flute; Middle Paleolithic Age; Upper Paleolithic Age; European Continent